Lady Chatterley's Legacy in the Movies : Sex, Brains and Body Guys. - Lehman, Peter; Hunt, Susan (New Brunswick, NJ : Rutgers University Press, 2010)
A new "body guy" genre has emerged in film during the last twenty years-a working-class man of the earth or bohemian artist awakens and fulfills the sexuality of a beautiful, intelligent woman frequently married or engaged to a sexually incompetent, educated, upper-class man. Lady Chatterley's Legacy in the Movies relates a host of wide-ranging films to a literary tradition dating back to Lady Chatterley's Lover and an emerging body culture of our time. The authors argue that the hero's body, lovemaking style, and penis-revealed through extensive male nudity-celebrate conform.
"Everything you are is between your legs" -- Rebels, outsiders, artists and -- brutes? -- "Fuck me like a cop, not a lawyer" -- "Brain work isn't much of a spectator sport" -- Hung like a horse -- or an acorn -- Unmaking love -- "Why do you say that as if it were a weakness? it's not."
Print version record.
Includes bibliographical references (pages 191-194) and index.
English.
JSTOR
Keywords: Sex role in motion pictures; Sex in motion pictures; Stereotypes (Social psychology) in motion pictures; Women in motion pictures; Men in motion pictures; Rôle selon le sexe au cinéma.; Sexualité au cinéma.; Stéréotypes au cinéma.; Femmes au cinéma.; Hommes au cinéma.; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- Reference; Men in motion pictures; Sex in motion pictures; Sex role in motion pictures; Stereotypes (Social psychology) in motion pictures; Women in motion pictures; Electronic book